MATHEMATICAL METHODS IN THE MODERN THEORY OF COGNITION AND MATHEMATICAL STYLE OF MENTALITY - L. D. Zhuleva (Научный вестник МГТУ ГА, 2016)
Mathematical methods of the modern theory of cognition are examined and the possibilities of applying mathematics in different fields of science are shown.